ROLE OF FAMILY SUPPORT ON THE REHABILITATION OF PERSONS WITH ALCOHOL ADDICTION IN NORTHERN CITY DIVISION OF MBALE CITY - NEUMBE REBBECCA (My University, 2024)
ABSTRACT The study contracted on role of family support on the rehabilitation of persons with alcohol addiction in northern City Division of Mbale City. The study concentrated on threse specific objectives of:To explore the various rehabilitation programs for persons with alcohol addiction in Northern City Division, Mbale City, to determine the role of family support in the rehabilitation of persons with alcohol addiction in Northern City Division, Mbale City and lastly to investigate factors hindering family support in the rehabilitation of persons with alcohol addiction in Northern City Division, Mbale City. The study used a qualitative research methodology and it considered a sample size of 15 participants. Study findings concluded that: individual counseling program is one of the rehabilitation programs for persons with alcohol addiction, Detoxification program is one of the rehabilitation programs for persons with alcohol addiction and this was revealed in study findings, that Family support plays a key role in fostering the initiation of recovery of alcohol addicted persons. In support of this finding and was reported by study participants during data collection, that family plays an important role in supporting successful changes in drinking behavior, that family conflict over day-to-day matters affects family involvement in the rehabilitation of persons with alcohol addiction. The study recommended that Government and stakeholders should put in place measures of controlling alcohol production, distribution and consumption, that Government in conjunction with local leaders should sensitize the population about the dangers of alcohol addiction and lastly that there is need to strengthen family relationships. This will go a long way in mitigating problems related to alcohol addiction.